2017
DOI: 10.1016/j.apgeog.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Environmental inequality and pollution advantage among immigrants in the United States

Abstract: Environmental inequality scholarship has paid little attention to the disproportional exposure of immigrants in the United States (U.S.) to unfavorable environmental conditions. This study investigates whether new international migrants in the U.S. are exposed to environmental hazards and how this pattern varies among immigrant subpopulations (e.g., Hispanics, Asian, European). We combine sociodemographic information from the American Community Survey with toxicity-weighted chemical concentrations (Toxics Rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…More broadly, studies have shown that immigrant groups face higher and disproportionate levels of exposure to environmental hazards than native born United States citizens (Bakhtiyarava and Nawrotzki, 2017). These findings mirror many other studies of place and environmental inequality, which find disproportionately higher environmental burdens are borne by communities of color and lower income populations (Tripolsky, 2014).…”
Section: Immigrant Detention and Environmental Impactssupporting
confidence: 58%
“…More broadly, studies have shown that immigrant groups face higher and disproportionate levels of exposure to environmental hazards than native born United States citizens (Bakhtiyarava and Nawrotzki, 2017). These findings mirror many other studies of place and environmental inequality, which find disproportionately higher environmental burdens are borne by communities of color and lower income populations (Tripolsky, 2014).…”
Section: Immigrant Detention and Environmental Impactssupporting
confidence: 58%
“…We identified 10 studies that investigated immigrant environmental disparities other than endogenous factors or air pollution. 75 84 Seven of the 10 studies were conducted in the United States. They examined environmental disparities in proximity to green spaces/parks, chemical concentrations, and residence within flooding zones.…”
Section: Resultsmentioning
confidence: 99%
“…them confirm the inequalities (e.g.Hernández et al, 2015, for Hispanics in Houston, Texas).Despite only focusing on exposure to industrial facility emissions,Bakhtsiyarava & Nawrotzki (2017) paper on the USA showed that immigrants tend to be less exposed to toxins, while in Boletín de la Asociación de Geógrafos Españoles, (92)…”
mentioning
confidence: 80%
“…have been found to suffer from a lower environmental quality too (e.g. Bakhtsiyarava & Nawrotzki, 2017;Cooper et al, 2019;Havard et al, 2011;Mitchell & Dorling, 2003;Moreno Jiménez, 2007;Raddatz & Mennis, 2012;Hernández et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%